2021
DOI: 10.20473/fmi.v57i4.11121
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy for Aseptic Splenic Abscess

Abstract: Highlight :A 26-year-old woman have sterile aerobic and anaerobic bacterial cultures.Pus and splenic tissue examination revealed no bacterial proliferation, while the surgery revealed a splenic abscess.Abstract:We presented a rare case, a 26-year-old woman have sterile aerobic and anaerobic bacterial cultures. Clinical examination of the patient showed a dense cystic mass in the left upper abdomen. Ultrasonography examination suspected a dermoid cyst. However, MRI examination of the abdomen showed turbid cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In septic condition there is a defect in cellular oxygen utilization, anaerobic metabolism occur and blood lactate level will increase as a result (Budipramana VS, 2021). An initial supportive therapy and parenteral broadspectrum antibiotics were prominently important to undertake while waiting for further diagnostics and therapies arrangements were made (Pranata AK, 2021). A statistical test using two independent t-tests on rabbit age and rabbit weight before surgery revealed that both were still homogeneous, indicating that differences in age and weight of rabbits before surgery did not cause bias.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In septic condition there is a defect in cellular oxygen utilization, anaerobic metabolism occur and blood lactate level will increase as a result (Budipramana VS, 2021). An initial supportive therapy and parenteral broadspectrum antibiotics were prominently important to undertake while waiting for further diagnostics and therapies arrangements were made (Pranata AK, 2021). A statistical test using two independent t-tests on rabbit age and rabbit weight before surgery revealed that both were still homogeneous, indicating that differences in age and weight of rabbits before surgery did not cause bias.…”
Section: Sample Characteristicsmentioning
confidence: 99%